La banda y la flor - Calderón de la Barca, Pedro, 1600-1681 (Calderón de la Barca, Pedro, 1600-1681. Plays (Pamplona, Spain), 2016)
The present edition of the comedy La banda y la flor by Pedro Calderón de la Barca is part of a critical edition devoted to the complete comedies by this author, funded by GRISO (Grupo Investigación Siglo de Oro), Universidad de Navarra, and under the direction of Prof. Dr. Ignacio Arellano. This volume contains the literary study of the comedy, the philological annotation, as well as the critical edition of the play itself.